Smart Greenhouse Design for Strawberry Cultivation in Pandanrejo, Batu City - Muhammad Arief Bustomi; Bachtera Indarto; Iim Fatimah; Suyatno4; Sudarsono; Yono Hadi Pramono (Jurnal Sosial Humaniora, 2023)
Batu City, which is famous as a tourist city, is not only an urban area. Mostof the Batu city area is a rural area, especially the northern area which isincluded in the Bumiaji sub-district. As a tourist area, Batu City has a largeenough economic potential to improve the welfare of its people. Most of thepeople of Batu city who live in rural areas are fruit and vegetable farmers.Pandanrejo village in Bumiaji sub-district is an example of a strawberryproducing village in Batu city. Various problems are faced by strawberryfarmers in Pandanrejo village. One of them is related to the uncertainweather conditions in their village. The ITS Physics department teamprovides solutions related to these weather conditions with an innovativeclimate conditioning technology that can be applied in agriculture. Thistechnology is a smart greenhouse in which there is control of environmentalconditions for strawberry plants. With the application of smart greenhousetechnology, it is expected to increase the productivity of strawberries and thewelfare of the farming community of Pandanrejo village, Batu city.